Depressive disorders, anxiety disorders and subjective mental health in common musculoskeletal diseases: A review. (September 2019) - Heikkinen, Jeremi; Honkanen, Risto; Williams, Lana; Leung, Janni; Rauma, Päivi; Quirk, Shae; Koivumaa-Honkanen, Heli
Highlights: Mental disorders and musculoskeletal diseases are major causes of disability. Mental disorders and subjective mental health are associated with common musculoskeletal diseases. Longitudinal studies are needed in order to understand the causal relationships. Abstract: Globally, musculoskeletal diseases (MSDs) and mental disorders are the leading causes of disability, but their mutual relationships have been little studied. The objective of the current review is to summarize the evidence on the relationships between depressive and anxiety disorders, subjective mental health and common MSDs in adults aged 45 years and over. A review of studies published in English, identified using MEDLINE, was conducted. Search terms included spinal stenosis, intervertebral disc displacement, osteoarthritis, osteoporosis, depressive disorder, anxiety disorders, mental health, subjective well-being, subjective quality of life, life satisfaction and personal satisfaction. A total of 287 records were initially identified, and an additional 190 records were identified from their reference lists. Eight studies were considered eligible and were, thus, included in the current review. The included studies reported that: 1) major depressive disorder is associated with chronic back pain; 2) anxiety disorders are associated with cervical or lumbar disc herniation; 3) mood and anxiety disorders are associated with lower bone mineral density in men; 4) life satisfaction and its improvement prevent bone loss in postmenopausal women; and 5) quality of life reduces progressively as the number of osteoporotic fractures increases. In conclusion, common MSDs are associated with mental disorders and subjective mental health in adults aged 45 years or more, but longitudinal research is needed.